The dynamics of government policy in handling Corona Virus Disease 2019 - Nurwita Ismail (Jurnal Hukum Volkgeist, 2020)
The implementation of PSBB or Lockdown still pay attention to the effects caused in the community. Making a regulation is not providing solutions but how to implement existing regulations. With the restrictions on community activities which basically will affect the financial factors. The government is not only thinking about how the country's economic problems the presence of the government is able to embrace all aspirations and give priority to the rights of its citizens. This research method uses a normative research approach. The data used are secondary data from Literature, Journals, and Others related to the Topic. Data analysis using qualitative analysis. The results of this study conclude that the implementation of policies illustrates how the existence of regulations clearly established by policy makers (government) that have certain impacts by taking into account the details of the program specifications, namely how and where the institution or organization should run the program, and how the law or program is interpreted . The government must think carefully about how resources are allocated, how budgets can be distributed, and who are the personnel responsible and implementing the program that should be clearly stated in a decision to be made by the government in its policies. If a variety of policies carried out by the government must be adjusted to the provisions of existing legislation so as not to cause the blurring of norms.